NON-ALCOHOLIC FATTY LIVER DISEASE IN CHILDREN - L.V. Chistova; T.E. Borovik; N.N. Semenova; A.N. Surkov; L.A. Ryzhkova; E.S. Zakharova (Union of pediatricians of Russia, 2010)
Metabolic syndrome that represents a totality of interrelated carbohydrate metabolism and lipid disorders, as well as a mechanism regulating arterial tension and endothelium function is one of the critical issues in pediatrics. In recent years, children with metabolic syndrome are increasingly diagnosed with liver injuries symptoms that are associated with a fatty transformation of the liver [1-3]. In this case, non-alcoholic fatty liver disease (NAFLD), a liver manifestation of metabolic syndrome is diagnosed. The diagnosis is confirmed in the absence of alcohol abuse in the past medical history, virus and autoimmune liver disease markers, elimination of toxic and drug influence, as wells as disorders of copper and iron exchange in the patient's system. One of the key risk factors for developing NAFLD in children is overeating and reduced physical activities. It was believed in the past that NAFLD is relatively benign, however, there is evidence in current literature that this is a pathological condition that may develop and result in extreme fibrotic alterations in the liver parenchymatous tissue all the way to cirrhosis and hepatocellular carcinoma [4]. Early-stage identification and timely launch of therapy for NAFLD in children represents one of the most important objectives in modern healthcare. Key words: metabolic syndrome, non-alcoholic fatty liver disease, children, steatohepatosis. (Pediatric Pharmacology. - 2010; 7(6):68-72)